Global and regional burden of nasopharyngeal cancer in older adults attributable to smoking and high alcohol use from 1990 to 2021 - Wang, Xiao; Li, Ying; Luo, Yujie; Song, Xin (Frontiers in Public Health, 2025)
BackgroundNasopharyngeal cancer (NPC) poses a considerable global health burden, with behavioral risk factors such as smoking and high alcohol use contributing to disparities across sociodemographic groups. The growing aging population faces heightened vulnerability to NPC due to prolonged exposure to these modifiable risks, yet comprehensive analyses of aging-specific burden patterns remain limited.MethodsUtilizing the Global Burden of Disease 2021 data, we conducted a systematic evaluation of NPC burden attributable to smoking and alcohol use across 204 countries from 1990 to 2021. Age-stratified analyses focused on older adults (≥60 years), incorporating three analytical dimensions: Sociodemographic Index (SDI) quintiles, sex-specific disparities, and geospatial heterogeneity. Age-standardized mortality (ASMR) and age-standardized DALY rates (ASDRs) were calculated with 95% uncertainty intervals. Temporal trends were quantified via estimated annual percentage changes (EAPCs). Bayesian age-period-cohort modeling projected disease burden through 2050.ResultsFrom 1990 to 2021, smoking and high alcohol use contributed substantially to the NPC burden globally, with older adults exhibiting distinct risk profiles. Decline in smoking-related burden in global ASDR was observed, yet older adults in low and middle SDI regions retained disproportionately high rates. Rise in alcohol-related burden in certain regions (e.g., Southeast Asia and Caribbean) was particularly pronounced among older age groups. Middle and high-middle SDI regions consistently exhibited the highest ASDR for both risk factors, with older adults contributing a significant share of disability-adjusted life years (DALYs). Older males faced the highest DALY burdens, with extreme older male-to-female disparities persisting across age groups. Population aging will amplify absolute DALY burdens among older adults by 2050.ConclusionBehavioral risk factors such as tobacco and alcohol use remain key contributors to the burden of nasopharyngeal cancer in older persons, with significant regional, gender, and demographic differences. There is an urgent need to develop targeted public health policies focusing on smoking cessation and alcohol control that take into account the health needs of older persons.